POLA PERUBAHAN KONSEPSI SISWA PADA MATERI HUKUM DASAR KIMIA MELALUI MODEL PEMBELAJARAN RADEC - Firyal Iftikhar Cikalkinanty, - (2023)
This research aims to obtain information about the implementation of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model in the basic laws of chemistry topic and students' mastery of concepts, together with patterns of students' conceptual changes in the basic laws of chemistry topic through the RADEC learning model. The research method used is pre-experimental, involving only one experimental group without a control group. The research design used is the one group pretest-posttest design, where the research begins with a pretest, followed by the implementation of the RADEC learning model, and concludes with a posttest. The participants in this research were 35 students from the 10th grade of a private high school in Bandung. The instruments used in this research include test equipment, observation sheets, and a self-assessment questionnaire. The results of the research show that the implementation of the RADEC learning model in the basic laws of chemistry scored 65 out of 100, categorizing it as moderately good. There was an improvement in students' mastery of concepts as seen from the average N-Gain value, which is 0.60, categorizing it as moderate. There was a pattern of positive changes in students' conceptions, dominated by the TP-P pattern (not understanding-partially understanding) with a frequency of 31.02%, TP-PS pattern (not understanding-partially understanding) with a frequency of 15.10%, PS-P pattern (partially understanding-partially understanding) with a frequency of 8.98%, and M-P pattern (misconception-partial understanding) with a frequency of 6.12%.